Synergistic effects of CO2 sequestration on mechanical, microstructural, and environmental performance in carbonated MgO-based ECC - Zihao Song; Rui Chen; Tianyu Wang; Haoliang Wu (Journal of CO2 Utilization)
Reactive magnesium oxide (MgO) cement (RMC) presents a promising approach to reducing CO2 emissions and mitigating environmental impacts in cement production. Owing to its capacity to form a durable, high-strength matrix, RMC is particularly suitable for producing Engineered Cementitious Composites (ECC) with enhanced structural integrity. This study leveraged RMC’s high carbonation potential to assess its influence on the sustainability and mechanical performance of carbonated MgO-based ECC. Specifically, the effects of varying MgO content on mechanical properties, crack patterns, and microstructure were investigated across six mix designs, with MgO dosages ranging from 40 % to 70 % of the binder, under both standard and accelerated carbonation curing conditions. Results indicated that higher MgO dosages improved compressive and flexural strengths, with CM0.7 (70 % MgO) achieving a compressive strength increase from 30.02 MPa to 63.62 MPa over 28 days. Microstructural analyses via SEM-EDS and XRD revealed carbonation-induced densification, enhancing crack control and fiber-matrix bonding. The study concludes that increasing MgO content enhances both the sustainability and mechanical resilience of carbonated MgO-based ECC, though optimal dosing is necessary to balance strength gains with dimensional stability. These findings underscore the potential of carbonated MgO-based ECC as an environmentally favorable option for sustainable construction applications.